Bimbingan Belajar Matematika Penjumlahan dan Pengurangan di Bimbel Baskara Dusun Krajan Sidoharjo Pulung Ponorogo Dengan Menggunakan Metode Jarimatika oleh Mahasiswa KPM INSURI Ponorogo Kelompok 8 - Rino Retnaning Siwi; Medina Nur Asyifa Purnama (Institut Agama Islam Sunan Giri Ponorogo, 2023)
The purpose of baskara tutoring in community service activities (KPM) is to improve student learning outcomes, at the elementary school level, in completing addition, subtraction, and multiplication operations using the Jarimatics method. In accompanying this activity the author uses the ABCD (Asset Based Community Development) approach. The ABCD method is the ABCD (Asset-Based Community Development) approach, which is a paradigm in community service, the principle of the ABCD approach is that everything leads to the context of understanding and internalizing assets, their potential, strength, and utilization independently and optimally. The result of this community service is to motivate children to learn mathematics during the school holidays, because they can learn while playing so that mathematics can be more fun. In addition to filling school holidays, this learning assistance activity is also to minimize children's use of gadgets or cellphones. Activities are carried out at night after the evening prayer, ending before the evening call to prayer.